PENETAPAN HARGA PENJUALAN GAS LPG BERSUBSIDI DI KECAMATAN MUTIARA DITINJAU MENURUT HUKUM ISLAM - Mariana Mariana (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This study aims to determine the pricing of subsidized LPG gas sales in the Mutiara District and how Islamic law views. This research uses descriptive analysis method, using observation, interview, and documentation techniques. The results of the study show the sale of subsidized LPG gas in Mutiara District at the base although it has made a profit from the price set but there is also a base still selling above the HET (Highest Retail Price) and prioritizing gas supply to retail traders and prices at retail traders even higher so that people are forced to buy because of household needs even though the price is expensive. Islamic law allows the determination of the price of 3 kg LPG gas for the achievement of benefits, but in reality, this has not been fully realized in its implementation. Therefore, it is hoped that the base will be able to comply with government regulations on the sale of subsidized LPG gas and to the government to tighten supervision on this matter.